Attack Intensity of Walang Sangit Pest on Rice Plant in The Area of Rubaru Agriculture Center, Sumenep District - Amirul Umam; Endang Triwahyu Prasetyawati (Future Science, 2022)
Walang sangit is one of the potential pests which at certain times becomes an important pest. These pests can cause yield losses of up to 50%. It is estimated that a population of 100,000 heads per hectare can reduce yields by up to 25%. This research on the intensity of the pest attack was aimed at knowing the categories of attacks on land owned by farmers in Karangnangka Village and finding out more environmentally friendly control methods. The number of plants observed every week was selected as many as 30 points (clumps) marked by pieces of bamboo or wood with a diagonal pattern. Data collection started by counting the number of plants in one clump at each sample point, then continued by counting the number of grains in each clump, and the last data was the number of seeds that were attacked or damaged in each clump. Then increase the attack intensity calculated using the absolute attack intensity formula. Calculations show a decrease every week, with values ??of 4.84%, 5.99%, and 6.60% sorted from the first observation to the third week. The control that can be applied is the use of animals (crabs) as traps to attract pests such as stink bugs.